Unbound Corneocyte Lipid Envelopes in 12R-Lipoxygenase Deficiency Support a Specific Role in Lipid-Protein Cross-Linking - Meyer, Jason M.; Crumrine, Debra; Schneider, Holm; Dick, Angela; Schmuth, Matthias; Gruber, Robert; Radner, Franz P.W.; Grond, Susanne; Wakefield, Joan S.; Mauro, Theodora M.; Elias, Peter M. (American Journal of Pathology, 2021)
Loss-of-function mutations in arachidonate lipoxygenase 12B (ALOX12B) are an important cause of autosomal recessive congenital ichthyosis (ARCI). 12R-lipoxygenase (12R-LOX), the protein product of ALOX12B, has been proposed to covalently bind the corneocyte lipid envelope (CLE) to the proteinaceous corneocyte envelope, thereby providing a scaffold for the assembly of barrier-providing, mature lipid lamellae. To test this hypothesis, an in-depth ultrastructural examination of CLEs was performed in ALOX12B−/− human and Alox12b−/− mouse epidermis, extracting samples with pyridine to distinguish covalently attached CLEs from unbound (ie, noncovalently bound) CLEs. ALOX12B−−/− stratum corneum contained abundant pyridine-extractable (ie, unbound) CLEs, compared with normal stratum corneum. These unbound CLEs were associated with defective post-secretory lipid processing, and were specific to 12R-LOX deficiency, because they were not observed with deficiency of the related ARCI-associated proteins, patatin-like phospholipase 1 (Pnpla1) or abhydrolase domain containing 5 (Abhd5). These results suggest that 12R-LOX contributes specifically to CLE–corneocyte envelope cross-linking, which appears to be a prerequisite for post-secretory lipid processing, and provide insights into the pathogenesis of 12R-LOX deficiency in this subtype of ARCI, as well as other conditions that display a defective CLE.
CRIS-Team Scopus Importer:2021-05-07